A83 THE MUCOSA-ASSOCIATED-MICROBIOTA IS ASSOCIATED WITH RELAPSE IN CROHN'S DISEASE PATIENTS UNDERGOING ILEOCECAL RESECTION. (1st March 2018) - Laffin, M; Perry, T; Park, H; Gillevet, P; Sikaroodi, M; Kaplan, G G; Fedorak, R; Kroeker, K I; Dieleman, L A; Dicken, B; Madsen, K
Abstract: Background: A large proportion of Crohn's disease patients require an intestinal resection at some point. The most common type of intestinal resection in CD patients is an ileocolonic resection (ICR). Unfortunately, following ICR, disease recurs at the anastomosis in up to 80% of subjects at one year. Evidence suggests that the fecal stream and its associated microbial contents play a central role in disease recurrence. Aims: The aim of this study was to define the mucosal-associated microbiota at the time of ICR and 6 months post-operatively and to determine if microbial community structure at the time of surgery was predictive of future disease relapse. Methods: Ileal biopsies were obtained at surgery and after 6 months from CD patients undergoing ICR (n=45). Composition and function of mucosal associated microbiota was assessed by 16S rRNA sequencing and PICRUSt analysis. Endoscopic recurrence was assessed using the Rutgeerts score. As a measurement of tissue disease activity, TNFα concentration was measured in ileal samples taken at the time of surgery using a Meso Scale discovery platform. To identify microbial composition and metabolic pathways with differentiating abundance in the different groups, the LDA (Linear Discriminant Analysis) Effect Size (LEfSe) algorithm was used with the online interface Galaxy. Results: At 6 months, 30 patients remained in remission while 15 had recurrent disease. Demographic data between the two groups was similar. At the time of surgery, LEFse analysis of mucosal biopsies showed Clostridiales to predict maintenance of remission while Enterobacteriales predicted disease recurrence. In addition, a greater proportion of microbial genes associated with aerobic respiration were present in biopsy samples taken at surgery from patients which went on to have disease recurrence. An increase in Lachnospiraceae from surgery to 6 months post-ICR was associated with remission. At the time of surgery there was no difference in α-diversity or degree of inflammation as measured by TNFα levels between the patients which remained in remission or had disease recurrence at 6 months. Conclusions: Specific mucosal-associated bacterial populations and gene content at the time of surgery are associated with maintenance of remission following ICR in subjects with CD, independent of inflammation. This identification of specific bacterial populations associated with maintenance of remission may enable the development of targeted therapies to alter gut ecology towards a specific profile and thus prevent post-operative recurrence of CD. Funding Agencies: None